IMPLEMENTATION OF EMPLOYMENT AGREEMENTS FOR HEALTH WORKERS IN PRIVATE HOSPITALS - Fahri Alpalah, Oka; Marlina, Tina; Yosi Andri, Gusti (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The company's activities are essentially a joint effort between employers and workers to grow the company and improve workers' welfare. This research was conducted based on the author's interest in finding out the implementation of the work agreement between midwives and Dera As-Syifa Hospital, where, based on the secondary data that the author obtained, the work agreement form is PKWT. The Manpower Law has stipulated that PKWT is only for jobs that are not permanent or core business. The problem in this study is :P First, we will discuss implementing the work agreement between Dera As-Syifa Hospital and Health Workers. Second, what are the legal consequences if the minimum wage paid is not by the UMP/UMK Brebes? This study uses a normative research method, namely legal research conducted by researching library materials or secondary data. Then, it continued with the collection of primary material data through direct interviews and observations as well as secondary materials obtained from literature studies in the form of law books, legal journals, and other literacy associated with the core of this research. The results of the study showed that PKWT used in the working relationship between midwives and Dera As-Syifa Hospital based on Permenkes 1199 of 2004, which regulates the employment relationship for health workers can be held with PKWT so that it is an exception to the provisions regulated in the Manpower Law along with the Job Creation Law and PP 35/2021. However, the implementation of PKWT at Dera As-Syifa Hospital is still not appropriate because there is still a probationary period of 4 months with salary deductions, so during the probationary period, the salary is not by the provisions of the minimum wage applicable in Brebes Regency. According to relevant regulations, companies that provide salaries below the minimum wage can be subject to sanctions and automatically change PKWT to PKWTT. However, such conditions do not affect the company; workers still receive such treatment.